(untitled) (IAHS Medical Journal, 2026)
Background: More Occurrence of retinopathy of prematurity in preterm low birth weight babies exposed to different risk factors in Ad-din NICU is reported. The aim was to assess the Proportion of ROP development in different risk factor exposed group in a large cohort of very preterm infants who were assisted in Ad-din NICU. Aim of this study is to identify the most common risk factor and the severity of Retinopathy of Prematturity (RoP). Materials and methods: This prospective study was carried out at the level-3 NICU of Ad-din Medical College Hospital Dhaka. 53 preterm low birth weight baby who are <36 weeks and low birth weight < 2.1 kg are screened from 1st January 2022 to 31st Deccember 2022 were screened for Retinopathy of Prematurity and data taken for risk factor like respiratory support and blood product transfusion and assessed need for Laser therapy or injection Avastin. Selected babies were screened conducted by special ROP instrument by ROP specialist professor of ophthalmology. Results: Total 53 preterm LBW babies who were < 36 wks and <2.1kg were screened. Most (11.3%) were stage-1 and Zone-ii ( 52.8%). Respiratory support mainly given most of the babies ( 64.15%) by Nasal Intermittent Positive Pressure Ventilation (NIPPV). Out of which 11.7% needed inj Avastin. 22.6% babies needed no respiratory support, out of these 8.3% baby needed inj Avastin. 50% baby of 02 by HFNC needed inj Avastin. 16.6% baby without any respiratory support needed inj Avastin. 11.3% baby need PRBC transfusion, out of which 33.3% baby needed inj Avastin. 86.7% babies need no blood product transfusion, out of these 8.6% babies needed inj Avastin. Conclusion: So from this study it is clear that though prematurity itself is a risk factor for ROP development .Oxygen therapy , blood product transfusion are major risk factor for ROP development. So causious oxygen therapy and avoid unnecessary blood product transfusion and respiratory support to prevent ROP. IAHS Medical Journal Vol 8(1), June 2025; 60-63